Public Private Partnership for Affordable Housing in Abuja Nigeria: A Review - Ahmed, Yahaya; Atan Bin Sipan, Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
A public-private partnership was recently recognized as an option to end the current crisis of housing shortages and affordable housing in the country by the Nigerian government in line with UN recommendations. This study aims to identify the challenges of PPP for the provision of affordable housing in Abuja. The study based on review found that PPP has not made any significant contribution in providing affordable housing; rather, it is suddenly changing towards providing housing for high- and middle-income earners. The paper reveals that the challenge of PPP for affordable housing provision is the acquisition and access to land, high dependence of foreign building materials, adequate housing finance, difficulty of accessibility to mortgage facilities and land titles, poor infrastructure facilities, and cost recovery, among others. It therefore suggests that the government should provide land at no cost, encouraging the use of local building materials at a low price, providing more financial institutions at little or no interest, establishing an effective mortgage system, and incorporating assisted self-help and incremental housing into the public-private housing delivery system to ensure better results. Consequently, there is a possibility for the government to develop a framework for PPP to achieve its dream by providing affordable housing in Abuja, Nigeria.